Study on applicability of microgroove erosion mitigation method based on stress–erosion coupling simulation. (October 2022) - Xu, Weipeng; Wang, Huakun; Yu, Yang; Sun, Zhenzhou; Li, Haoda; Zhao, Yan; Fu, Yiqin
Abstract: Consideration of stress concentration is inevitable for local areas with a geometry discontinuity; therefore, this study was focused on the erosion mitigation performance of microgroove structures under the coupling of an applied stress and fine particle erosion. First, a modified stress-accelerated erosion model with high accuracy was developed. Subsequently, the erosion characteristics of microgrooves with different surface textures (rectangular, V-shape, and elliptical groove) were carefully studied based on the established multiphysics coupling simulation method. The effects of various parameters—groove width to groove depth ratio, incident angle, and magnitude of the applied stress—on erosion were also systematically investigated. The results showed that the impact angle and the applied stress had major effects on the erosion rates of the microgroove structures and that a rectangular groove was more suitable for stressed structures affected by erosion damage compared to the other groove types. Highlights: A modified Stress-accelerated erosion model was proposed. The erosion characteristic of micro-groove structure under the coupling of applied stress and particle erosion was analyzed. The effect of various factors on the erosion mitigation efficiency of micro-groove was systematic studied. The best configuration of textured structure was determined based on the stress-erosion coupling analysis.